Facing the Challenges of e-Government in Indonesia: Demographic Inequalities - Arief Rahman (The Indonesian Journal of Accounting Research, 2014)
Abstract: E-government readiness in Indonesia showed no improvement from year to year, indicating that the implementation of e-government is encountering serious problems. Despite the lack of empirical evidence, it is stated that one of them is digital inequalities or also known by the term of the digital divide. This research paper aims to investigate the impact of demographic disparities, represented by gender, age, and place of residence, on e-government use in Indonesia. In doing so, a structural equation model was proposed based on literature review and examined through survey research. Data were collected from a survey of 237 e-government users in Indonesia. The study took place in Sleman and Tulungagung regencies. The PLS (Partial Least Square) method was applied by using SmartPLS to estimate the research model. Smith-Satterwait test was employed to examine the moderating effect. The results show that digital inequalities, particularly age and place of residence, are significant problems in Indonesia, which should be resolved to improve the usage of e-government. The research is vital for scholars to give empirical evidence of digital inequalities and its impact on e-government use, especially in Indonesia. For the local governments, this research may contribute to policy-making in improving the e-government readiness.Abstrak: Kesiapan e-government di Indonesia tidak menunjukkan peningkatan dari tahun ke tahun, menunjukkan bahwa implementasi e-government menghadapi masalah serius. Meskipun kurangnya bukti empiris, itu menunjukkan bahwa salah satunya adalah ketidaksetaraan digital atau juga dikenal dengan istilah kesenjangan digital. Makalah penelitian ini bertujuan untuk menyelidiki dampak ketidaksetaraan demografis, diwakili oleh jenis kelamin, usia dan tempat tinggal, pada penggunaan e-government di Indonesia. Dengan demikian, model persamaan struktural diusulkan berdasarkan tinjauan pustaka dan diperiksa melalui penelitian survei. Data dikumpulkan dari survei terhadap 237 pengguna e-government di Indonesia. Penelitian berlangsung di kabupaten Sleman dan Tulungagung. Metode PLS (Partial Least Square) diterapkan dengan menggunakan SmartPLS untuk memperkirakan model penelitian. Tes Smith-Satterwait digunakan untuk menguji efek moderasi. Hasilnya menunjukkan bahwa kesenjangan digital, khususnya usia dan tempat tinggal, adalah masalah yang signifikan di Indonesia, yang harus diselesaikan untuk meningkatkan penggunaan e-government. Penelitian ini penting bagi para sarjana untuk memberikan bukti empiris ketidaksetaraan digital dan dampaknya pada penggunaan e-government, khususnya di Indonesia. Untuk pemerintah daerah, penelitian ini dapat berkontribusi pada pembuatan kebijakan dalam meningkatkan kesiapan e-government.